Chemical Composition, Molecular Docking Analysis, and Biological Properties of Salvia Mirzayanii - Rahman Mahdizadehdehosta; Hamid Shahbazmohammadi; Soheila Moein; Nepton Soltani; Kianoosh Malekzadeh; Mahmoodreza Moein (Advanced Biomedical Research)
Background: Diabetes is a dangerous metabolic disorder that is becoming more common worldwide. In the present research, we aimed to analyze the chemical composition, in silico molecular docking, and evaluate the biological features of Salvia mirzayanii. Materials and Methods: The constituents found in the aqueous extract of S. mirzayanii leaves were identified using gas chromatography–mass spectrometry (GC-MS). The major compounds of S. mirzayanii extract were subjected to molecular docking analysis. Screening for potential antioxidant abilities was conducted using radical scavenging assays. Alpha-amylase and α-glucosidase inhibitory kinetic studies were performed to evaluate the in vitro antihyperglycemic potential of S. mirzayanii. The in vivo function of S. mirzayanii extract was evaluated by examining the gene expression of phosphoenolpyruvate carboxykinase (PEPCK), glucose 6-phosphatase (G6Pase), and glucose transporter-4 (GLUT4) in diabetic rats. Results: The major compounds in aqueous extract of S. mirzayanii were 1,8-cineole (51.6 + 2.7%), linalool acetate (22.0 + 1.9%), a-terpinyl acetate (9.3 + 0.7%), and aromadendrene (5.6 + 0.6). In silico studies indicated that 1,8-cineole was a more potent inhibitor of α-amylase and α-glucosidase enzymes. The liquid extract of S. mirzayanii showed considerable radical scavenging activity against 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and effective inhibition of α-amylase (IC50 = 0.01 ± 0.02) and α-glucosidase (IC50 = 0.11 ± 0.01). The highest antihyperglycemic activity was observed with a 600 mg/kg dose of the plant’s aqueous extract. Conclusions: Altogether, our findings show the possibility of applying the aqueous extract of S. mirzayani leaves as a potential therapeutic compound.